MUSLIM IDENTITY AND ENGLISH LANGUAGE TEACHING - Ella Masita (Jurnal Scientia, 2022)
The article is a literature study addressing the conceptualization of Muslim identity specifically in relation to the teaching of English language at schools. It begins with the conceptualization of spirituality and how it differs from religion. Moreover, this article views religious identity as a part of social identity. Therefore, the next discussion is about how religious identity is understood in the context of English language teaching with a specific focus on Muslim identity. In doing so, three interrelated elements of Muslim identity are explored, namely religious beliefs, religious knowledge, and religious practices. Then, a number of challenges in teaching English language for Muslim people are also illustrated. Moreover, the remaining section of this article highlights the specific insight of efforts in maintaining Muslim students’ religious identity including how to minimalize the negative impacts of English teaching towards the development of religious identity. Finally, some conclusions are drawn.